Rewarding project development success - Kunkel, J. Gregory
J. Gregory Kunkel examines how major U.S. companies design their compensation and reward systems in support of their product development efforts.
Among select U.S. companies, best practices modify standard pay programs to reinforce a company-wide commitment to success.
Although much is known about successful management practices that accelerate the product development effort and lead to product success, relatively little research has been conducted to explore those compensation and reward practices that best support the product development effort. This article summarizes the "best practices" of selected major U.S. companies regarding the design of their compensation and reward systems in support of the product development effort. The research indicates that although traditional compensation and reward systems may be used to support the product development effort, these systems must be modified to ensure management commitment to the process, a culture of innovation and risk-taking, teamwork, and discipline in meeting product development milestones.
Keywords: Product development